O conhecimento profissional e a abordagem do ensino da probabilidade: um estudo de caso - Corrêa, Marcio Welker (2010)
This present research refers to a case study from the teaching speech on its practice, and not because of the observation of this, and aims to recognize as the professional knowledge of the mathematics teacher influences the approach of the probability in his classes. For this we compiled our theoretical picture from a bibliographic review, which contains the dissertations, theses, books and articles more closely related to our research. We used as a diagnostic tool semi-structured interviews that allowed to deep our questions in a process involving the dialogical. For the choice of six teachers subject of our research, we use the facts they have attended full degree in mathematics, are formed by the same educational institution in the period from 1998 to 2002 and have obtained formation as much in the discipline Probability as in the discipline Statistics, with the same teachers. Such criteria were used to construct a data set, in order to the control variables were well identified. In our results we could observe that the teaching of probability, characterized by a deterministic view of mathematics (formal approach) becomes an obstacle since it develops in different perspectives dialectically linked. Limit it to a single approach doesn't contribute to the acquisition of a way of thinking different from the logic dichotomous of yes/no, in which dominates the doubt, middle field where the probability operates